2014
DOI: 10.1002/hec.3027
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Alcohol on the Consumption of Hard Drugs: Regression Discontinuity Evidence from the National Longitudinal Study of Youth, 1997

Abstract: This paper estimates the effect of alcohol use on consumption of hard drugs using the exogenous decrease in the cost of accessing alcohol that occurs when individuals reach the minimum legal drinking age. By using a regression discontinuity design and the National Longitudinal Study of Youth 1997, I find that all measures of alcohol consumption, even alcohol initiation increase discontinuously at age 21 years. I also find evidence that consumption of hard drugs decreased by 1.5 to 2 percentage points and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 31 publications
1
54
0
Order By: Relevance
“…Consistent with the hypothesis that marijuana and alcohol are substitutes, there is evidence that marijuana participation falls sharply when individuals reach the minimum legal drinking age (Crost and Guerrero, ) but the relationship between marijuana consumption and crime is still debated (Morris et al ., ) . A number of previous studies have examined the relationship between alcohol and the use of illicit drugs other than marijuana (Petry, ; Sumnall et al ., ; Jofre‐Bonet and Petry, ; Conover and Scrimgeour, ; Deza, ) but their results have been decidedly mixed.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the hypothesis that marijuana and alcohol are substitutes, there is evidence that marijuana participation falls sharply when individuals reach the minimum legal drinking age (Crost and Guerrero, ) but the relationship between marijuana consumption and crime is still debated (Morris et al ., ) . A number of previous studies have examined the relationship between alcohol and the use of illicit drugs other than marijuana (Petry, ; Sumnall et al ., ; Jofre‐Bonet and Petry, ; Conover and Scrimgeour, ; Deza, ) but their results have been decidedly mixed.…”
Section: Introductionmentioning
confidence: 99%
“… 2 In similar studies, Crost and Guerrero () and Deza () find evidence that the additional consumption of alcohol has a displacement effect on the use of marijuana and the use of harder drugs, respectively. See also the debate between Crost and Rees () and Yörük and Yörük (2011; ) who come to different conclusions on whether alcohol and illegal drugs are complements while using the same data.…”
mentioning
confidence: 99%
“…Others have found that drug use tends to decline once youth reach the legal drinking age, suggesting short-term substitution (Deza, 2014). Although we did not examine short-term substitution or complementarity during adolescence or young adulthood, our results suggest long-term complementarity and support the argument that allowing access to alcohol during adolescence could lead to more drug use problems in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…A study of Australian survey data from 1988-1995 found that an increase in the price of alcohol increased the probability of marijuana use (Cameron and Williams, 2001). When examining the immediate effects of discontinuity of alcohol availability created by the current MLDA of 21 years on drug use among young adults, as alcohol consumption increased at age 21, there was a sharp decrease in consumption of hard drugs and marijuana (Crost and Guerrero, 2012; Deza, 2014) or no significant changes in marijuana use (Crost and Rees, 2013; Yörük and Yörük, 2013). …”
Section: Introductionmentioning
confidence: 99%